Use of High Performance Computing in Numerical Simulations : Book of Abstracts - 82nd International Scientific Conference of the University of Latvia (My University, 2024)
The 82nd International Scientific Conference of the University of Latvia. Use of High Performance Computing in Numerical Simulations. Book of Abstracts
Augstas veiktspējas skaitļošanas izmantošana skatliskā modelēšanā
Keywords: High performance computing; Research Subject Categories::NATURAL SCIENCES::Physics::Other physics; brīvo virsmu modelēšana; Ūdeņraža ražošana; kvantu gāzu skaitliskā modelēšana; Siltuma apmaiņas skaitliska analīze; Gaisa dezinfekcija; hidroģeoloģiskās modelēšanas pieeja; HEMUS superdators